2020
DOI: 10.2147/ijwh.s241785
|View full text |Cite
|
Sign up to set email alerts
|

<p>Exploring the Relationship Between Maternal Circulating Hormones and Gestational Weight Gain in Women Without Obesity: A Cross-Sectional Study</p>

Abstract: Background: Central homeostatic regulation of fat stores is attenuated during pregnancy, to allow for adequate fat deposition to support fetal development and lactation. What factors particular to pregnancy facilitate fat accumulation, and why gestational weight gain (GWG) is so variable, are not clear. The aim of this cross-sectional study was to examine the associations between GWG and circulating hormones with known effects on appetite and growth. Methods: Women without obesity (body mass index, BMI <30 kg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…For GWG, Lappas et al. ( 30 ) found no significant relationship, but described a trend toward lower PRL at delivery among non-obese, non-diabetic women in whom GWG exceeded recommended thresholds (compared with women with GWG within recommended ranges). The remaining two studies found no significant relationships between maternal PRL (measured at 16 and 27 weeks) and either pre-pregnancy BMI or GWG across a combined cohort of Chinese and Caucasian American women ( 32 ) or in a subset of the Caucasian American women only ( 29 ), after adjustment for multiple covariates.…”
Section: Resultsmentioning
confidence: 99%
“…For GWG, Lappas et al. ( 30 ) found no significant relationship, but described a trend toward lower PRL at delivery among non-obese, non-diabetic women in whom GWG exceeded recommended thresholds (compared with women with GWG within recommended ranges). The remaining two studies found no significant relationships between maternal PRL (measured at 16 and 27 weeks) and either pre-pregnancy BMI or GWG across a combined cohort of Chinese and Caucasian American women ( 32 ) or in a subset of the Caucasian American women only ( 29 ), after adjustment for multiple covariates.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, women with EWG showed a tendency to higher leptin levels than the AWG group ( p = 0.087), which is probably related to abnormal accumulation of body fat. Accordingly, several studies have reported that high leptin levels in the 2nd and 3rd trimester of pregnancy correlate with EWG [35, 45-47]. In contrast, Patro-Małysza et al [48] did not find differences in leptin concentration after delivery between AWG and EWG women.…”
Section: Discussionmentioning
confidence: 98%
“…Here, we investigated the maternal serum concentration of steroid hormones of F0 at 19 dG, resulting in increased progesterone and corticosterone and a decreased estradiol in the MO group compared to C, without changes in testosterone. The increased concentration of progesterone and the decreased concentration of estradiol in F0 MO group could be associated with the control of maternal body weight homeostasis to accommodate the fat deposition required to support fetal development and lactation, as well as deleterious maternal and placental functions ( Zambrano et al, 2005 ; Lappas et al, 2020 ). The increased concentration of corticosterone in F0 MO group is consistent with our previous data before gestation and at the end of lactation, confirming that high serum concentrations of this glucocorticoid are a common featuring of response to stress generated by maternal obesity that repercusses on developmental programming ( Zambrano et al, 2015 ; Rodríguez-González et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%